Efficiency Determinants and Dynamic Efficiency Changes in Latin American Banking Industries - Hassan, M. Kabir (2013)
This paper investigates the determinants of efficiency and dynamic efficiency changes across Latin American banking industries during recent periods of financial liberalization. Allocative, technical, pure technical, and scale efficiency measures are calculated and analyzed for seven Latin American countries. Consistent with extant literature, profit inefficiency is higher than cost inefficiency across our sample, suggesting that most of the profit inefficiency comes from the revenue side. The decomposition of revenue efficiency into revenue allocative efficiency and technical efficiency suggests that the source of inefficiency is regulatory (allocative) rather than managerial (technical). Moreover, consistent with what practitioners would expect, efficient banks have lower overhead costs relative to total income, use resources better, have higher quality portfolios, and have higher earnings (e.g., higher return on assets – ROA and return on equity – ROE) than inefficient ones. Furthermore, financial liberalization has brought productivity increases throughout Latin America; but this increase in productivity is a consequence of technological progress rather than enhanced technical efficiency.